PENGEMBANGAN NILAI KARAKTER MELALUI PROSES PEMBELAJARAN DI KELAS IV SD NEGERI 8 BANDA ACEH - Nurhaidah M. Insya Musa (Jurnal Pesona Dasar, 2019)
The education movement in schools should be able to strengthen the character of students through affective, cognitive and psychomotor harmonization in the learning process. The problems addressed in this research are: 1) How is the development of character value in the learning process in class IV elementary School Negeri 8 Banda Aceh? 2) What are the difficulties faced by teachers in developing character values in the learning process in class IV elementary School Negeri 8 Banda Aceh? This research aims to describe the development of character values and difficulties faced by teachers in the learning process in grade IV of SD Negeri 8 Banda Aceh. The approach used is qualitative research with a type of descriptive research. The subject in this study was 1 teacher and 38 students. The data collection techniques in this study are observations and interviews. Data analysis techniques used are data reduction, data presentation, and withdrawal of conclusions. The results of the development of character values in the learning process in class IV elementary School 8 Banda Aceh have been good, teachers always develop the value of students ' character through values of honesty, discipline, courtesy and courtesy, cooperation, responsibility, and In the learning process in the classroom and outside of class.  Guru Selau to develop character values in each learning process continuously. As for the difficulties teachers face on the development of character values in the learning process is because of the number of students in the classroom so that teachers are difficult to develop those values because not all students get noticed The same individual. But teachers always give students a moral message in a classical, developing character values both in the classroom and out of class so that they become students of good behavior. Conclusion of this research is teachers have developed values of honesty, discipline, courtesy and courtesy, cooperation, responsibility, and mutual respect, and others well in class IV elementary School 8 Banda Aceh.